Tinjauan Hukum Mengenai Unsur Kelalaian Dalam Kematian Ternak Sapi di Desa Laerung: Analisis Yuridis-Empiris Berdasarkan Perbuatan Melawan Hukum - Ismail Ali; Faizal Pratama; Dian Sabrina; Yuliani (Yayasan Pengembangan Sumber Daya Insani Lamaddukelleng, 2026)
This study aims to evaluate the manifestation of negligence (culpa) in cattle deaths in Laerung Village through the lens of Articles 1365 and 1367 of the Civil Code (KUHPerdata). Livestock deaths in rural areas are often viewed as ordinary agricultural incidents, but legally, they carry significant complexities of civil liability. Using empirical legal research methods, this study identifies that the ambiguity of the boundaries between